2017
DOI: 10.5888/pcd14.170343
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-Community Partnerships to Identify Patients With Food Insecurity and Address Food Needs

Abstract: IntroductionMore than 42 million people in the United States are food insecure. Although some health care entities are addressing food insecurity among patients because of associations with disease risk and management, little is known about the components of these initiatives.MethodsThe Systematic Screening and Assessment Method was used to conduct a landscape assessment of US health care entity–based programs that screen patients for food insecurity and connect them with food resources. A network of food inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 18 publications
(15 reference statements)
3
56
0
Order By: Relevance
“…Some clinical organizations have begun to screen and intervene for food insecurity. A review of these efforts 25 identified several commonly applied interventions including (1) referral to a list of resources such as federal benefit programs or food pantries (sometimes co-located); (2) assistance with federal benefits enrollment from case managers, social workers, or navigators; (3) immediate food provision from on-site gardens or stocks of food; and (4) produce vouchers that can be redeemed at food markets.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical organizations have begun to screen and intervene for food insecurity. A review of these efforts 25 identified several commonly applied interventions including (1) referral to a list of resources such as federal benefit programs or food pantries (sometimes co-located); (2) assistance with federal benefits enrollment from case managers, social workers, or navigators; (3) immediate food provision from on-site gardens or stocks of food; and (4) produce vouchers that can be redeemed at food markets.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts are increasing to address individuals' social needs as a strategy to address social determinants, although these approaches only indirectly address structural issues. [43][44][45][46] For example, some schools provide breakfast to address the social need for healthy food among individual students. However, to sufficiently address the affordability of healthy foods at the population level, social determinants such as food deserts must be addressed.…”
Section: Living Environmentsmentioning
confidence: 99%
“…Clinical programs and systems to screen for and intervene on food insecurity are being scaled across the United States. A 2017 review identified 22 healthcare entities that have implemented systematic food‐insecurity screening programs for older adults . Kaiser Permanente Colorado and Hunger Free Colorado, for instance, entered into a partnership in 2011, leveraging their unique assets to screen patients for food insecurity during clinical visits, refer food‐insecure patients to community specialists with expertise in community and federal nutrition programs, and support enrollment in appropriate programming…”
Section: Opportunities/early Successesmentioning
confidence: 99%